Genotype Profile of Global EYS-Associated Inherited Retinal Dystrophy and Clinical Findings in a Large Chinese Cohort - Xu, Ke; Chen, De-Fu; Chang, Haoyu; Shen, Ren-Juan; Gao, Hua; Wang, Xiao-Fang; Feng, Zhuo-Kun; Zhang, Xiaohui; Xie, Yue; Li, Yang; Jin, Zi-Bing (Frontiers in Cell and Developmental Biology, 2021)
Purpose The aim of this study was to probe the global profile of the EYS-associated genotype-phenotype trait in the worldwide reported IRD cases and to build a model for predicting disease progression as a reference for clinical consultation. Methods This retrospective study of 420 well-documented IRD cases with mutations in the EYS gene included 39 patients from a genotype-phenotype study of inherited retinal dystrophy (IRD) conducted at the Beijing Institute of Ophthalmology and 381 cases retrieved from global reports. All patients underwent ophthalmic evaluation. Mutations were revealed using next-generation sequencing, followed by Sanger DNA sequencing and real-time quantitative PCR analysis. Multiple regression models and statistical analysis were used to assess the genotype and phenotype characteristics and traits in this large cohort. Results A total of 420 well-defined patients with 841 identified mutations in the EYS gene were successfully obtained. The most common pathogenic variant was a frameshift c.4957dupA (p.S1653Kfs∗2) in exon 26, with an allele frequency of 12.7% (107/841), followed by c.8805C > A (p.Y2935X) in exon 43, with an allele frequency of 5.9% (50/841). Two new hot spots were identified in the Chinese cohort, c.1750G > T (p.E584X) and c.7492G > C (p.A2498P). Several EYS mutation types were identified, with CNV being relatively common. The mean age of onset was 20.54 ± 11.33 (4–46) years. Clinical examinations revealed a typical progression of RPE atrophy from the peripheral area to the macula. Conclusion This large global cohort of 420 IRD cases, with 262 distinct variants, identified genotype-phenotype correlations and mutation spectra with hotspots in the EYS gene.